Kajian Hukum Pengelolaan Sampah (Studi Kasus Lingkungan Pasar Inpres Matawai Sumba Timur) - Essy Windy; Rambu H Indah; Rambu Susanti M.Maramba (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2022)
The main problem raised in this paper is how is the legal protection of environmental pollution of the community around the market in the Matawai environment of Waingapu City, East Sumba Regency which is reviewed based on Law No. 18 of 2008 concerning Waste. The research method used is the type of empirical juridical research. This type of research uses a social-legal approach. This approach requires the disciplines of social science and law to examine the existence of positive law, as well as to look directly at each particular legal event that occurs in society. The results of the research in the Matawai press market that there is a lot of garbage that is thrown around the market location, caused by the lack of awareness of the traders about the cleanliness of the market by throwing garbage indiscriminately or not in its place. As a result of the waste being dumped in the environment, disturbing the comfort, health of the community around the market and violating the rights (Ukrainian 1945, article 28 (h) paragraph 1). So to protect the environment and the rights of the community, it is necessary to have legal protection. The legal protection provided by the State is then used as a legal guarantee for the community, in this case the community around the market affected by environmental pollution that occurred in the Matawai Inpres market. Legal protection efforts are in the form of administrative sanctions, civil sanctions and sanctions based on Law Number 18 of 2008 concerning Waste Management.